Surplus-Population and the Political Economy of Fear. (September 2019) - Azeri, Siyaves
Fear, of which the fear of death is a variation, can be analysed in its relation to forms of societies. Pertaining to Marx's concept of 'surplus-population' and his analysis of the capitalist law of population, it is argued that the main source of anxiety and fear in capitalist society is the fear of life, which is expressed in the form of fear of the dead and of monsters. Capital posits the identity of every human individual through its law of population. What humans fear the most is the life that they live, which turns them into walking dead. Human's fear of life is twofold: on the one hand, she fears from being posited a zombie, a piece within the pile of human trash, that is, the surplus-population; on the other hand, she is scared of the dead, capital the spectre, which vampire-like sucks upon living labour.